La importancia del uso de efectos isotópicos de átomos pesados para determinar mecanismos de reacción en la activación de moléculas pequeñas - Ángeles-Boza, Alfredo M. (2017)
The determination of isotope effects is an important tool in the study of chemical transformations. Very common in the literature is the use of deuterium isotope effects, which is typically covered in many textbooks. Unfortunately, heavy atom isotope effects have not received the same attention despite its great relevance. This article will serve as an introduction to this very important topic.